We are the Brennans [large type] - Lange, Tracey (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"When twenty-nine-year-old Sunday Brennan wakes up in a Los Angeles hospital, bruised and battered after a drunk driving accident she caused, she swallows her pride and goes home to her family in New York. But it's not easy. She deserted them all--and her high school sweetheart--five years before with little explanation, and they've got questions. Sunday is determined to rebuild her life back on the east coast, even if it does mean tiptoeing around resentful brothers and an ex-fiancé. The longer she stays, however, the more she realizes they need her just as much as she needs them. When a dangerous man from her past brings her family's pub business to the brink of financial ruin, the only way to protect them is to upend all their secrets--secrets that have damaged the family for generations and will threaten everything they know about their lives. In the aftermath, the Brennan family is forced to confront painful mistakes--and ultimately find a way forward, together"--